2018
DOI: 10.1016/j.amsu.2018.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic common bile duct exploration; a preferential pathway for elderly patients

Abstract: BackgroundLaparoscopic common bile duct exploration (LCBDE) has emerged as a recommended alternative to endoscopic retrograde cholangiopancreatography (ERCP) for the management of choledocholithiasis. However, its use in the elderly has been limited, and evidence of its safety and efficacy in these patients is yet to be established. This study describes our experience of LCBDE in elderly patients, analysing the safety and efficacy of this technique in comparison to younger patients.MethodsAll patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Several studies have reported the recurrence of CBDS after removal procedure and operations. Platt et al said the stone clearance rate was 96.7% in LCBDE, 90% in ERCP [14]. In a long-term follow-up study, Lee et al reported 5.9% of the recurrence rate of CBDS after LCBDE [15].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the recurrence of CBDS after removal procedure and operations. Platt et al said the stone clearance rate was 96.7% in LCBDE, 90% in ERCP [14]. In a long-term follow-up study, Lee et al reported 5.9% of the recurrence rate of CBDS after LCBDE [15].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of endoscopic technique, ERCP is considered a preferred therapeutic method in management of CBD stones. However, it can be still challenging in some cases, such as high total hospital expenses and high risk of post-ERCP complications[21,22]. CP, one of the main modes to standardize treatment and care, is increasingly adopted by hospitals to strive to better outcomes and lower costs.…”
Section: Discussionmentioning
confidence: 99%
“…Como conducta quirúrgica, para los 58 casos de coledocolitiasis; se realizó CPRE (colangioretrograda endoscópica) en 49 (84,48%) casos; y se terminó el tratamiento con una colecistectomía simple en 32 (55,17%) casos, colecistectomía más CIO (colangiografia intraoperatoria) en 9 (15,52%) casos y 1 (1,72%) caso requirió derivación biliodigestiva. Este manejo es diferente al manejo de otros centros, donde la coledocolitiasis diagnosticada preoperatoria o hallada en el intraoperatorio durante la colecistectomía, se resuelve en el mismo acto quirúrgico, con una exploración de la vía biliar por el conducto cístico o coledocotomía (31,31) . Existe varios estudios al respecto, sobre la ventaja o desventaja de la cirugía abierta o laparoscópica en comparación con la CPRE (1,(27)(28)(29)(30)32) .…”
Section: Discussionunclassified